The importance of identifying and protecting coastal wildness - Gleason, Mary G.; Reynolds, Mark D.; Heady, Walter N.; Easterday, Kelly; Morrison, Scott A. (Frontiers in Conservation Science, 2023)
Conservation of coastal biodiversity and associated ecosystem services requires protection and management for attributes of coastal wildness, which we define to include physical and ecological intactness and connectivity, native species and habitat diversity, and limited human disturbance. Coastal wildness is threatened by high demand for access to and development of coastal margins; sea level rise exacerbates this threat. As a case study, California (USA), a biodiversity hotspot, has a network of marine and terrestrial protected areas along the coast and strong coastal policy. While 35% of California's coast has wildness attributes, only 9% of California's coast is characterized as wild and also protected on both land and in the adjacent waters. A multi-tiered approach is needed to incorporate wild coast attributes into conservation planning and protection of coastal areas. A coastal wildness designation is needed, as well as policies that manage for wildness attributes in existing protected areas.